Toward building a competency model for sustainability in school-based civic education workshops: the ComPeDiSo - Pignalberi, Claudio (Form@re - Open Journal per la formazione in rete, 2024)
The article addresses the topic of ecological transition and sustainable development in education and the new professional skills required of the student, particularly civic engagement. Starting with an analysis of recent studies in the pedagogical field (sustainable development, ecological thinking and sustainable skills), with a focus on the ONU Agenda 2030, the article presents the ComPeDiSo (personal, disciplinary-methodological and social competencies) model drafted, and administered to a sample-test of 98 students, in a secondary school in Rome. The model was used in the civic education workshops as an area that, to date, lacks solid planning by teachers and, at the same time, does not provide a set of skills useful to the student for his or her formative growth. Verso la costruzione di un modello di competenze per la sostenibilità nei laboratori di educazione civica nella scuola: il ComPeDiSo. L’articolo affronta il tema della transizione ecologica e dello sviluppo sostenibile in ambito educativo e le nuove competenze professionali che si richiedono allo studente, in particolare il civic engagement. A partire da un’analisi dei recenti studi in ambito pedagogico (sviluppo sostenibile, pensiero ecologico e competenze sostenibili), con un focus sull’Agenda 2030 dell’ONU, l’articolo presenta il modello ComPeDiSo (competenze personali, disciplinari-metodologiche e sociali) redatto e somministrato ad un campione-test di 98 alunni/e, in una scuola secondaria di secondo grado di Roma. Il modello è stato utilizzato nei laboratori di educazione civica in quanto area che, ad oggi, risulta carente di una solida progettazione da parte dei docenti e, allo stesso tempo, non fornisce un bagaglio di competenze utili allo studente per la sua crescita formativa.